واقع التأمين البنكي في الجزائر من ( 2011-2022) - هارون معامرة; سليم بوزنة; عمر غمام علي (جامعة الوادي university of eloued, 2024)
" انعكست العولمة على أداء البنوك، أدت إلى انتشار فكرة البنوك العالمية، مما يعني توسع العمل المصرفي ودخوله في العديد من المجالات التي ارتبطت بالوساطة المالية الأخرى، وجمع العديد من الأعمال في قسم واحد تنشر المخاطر وتواجه المنافسة. تهدف هذه الدراسة إلى التعرف على واقع التأمين البنكي كآلية تتبعها شركات التأمين لتوزيع منتجاتها التأمينية عبر البنوك، بالإضافة إلى أهم الاتفاقيات التي تربط البنوك مع شركات التأمين الناشطة في السوق الجزائرية، مبرزين أهم المزايا التي تميز التأمين البنكي وكذا واقعه في الجزائر خلال الفترة الممتدة من2011 2022 وتوصلت الى النتائج الحصة الأكبر حققتها اتفاقية صندوق SAA التأمينات تحت سيطرة فرعين كبيرين هما فرع السيارات وفـرع تأمين أضرار الممتلكات، إذ نرى كل سنة هيمنة واضحة لهذين الفرعين حيث يستحوذان على مـا يفـوق 83 %من الأقساط، وارتفعت النسبة إلى أكثر من 80 %منذ سنة 2011 إلى غاية 2022." "Globalization was reflected in the performance of banks. It led to the spread of the idea of global banks, which meant the expansion of banking work and its entry into many areas that were linked to other financial intermediation, and the gathering of many businesses in one department that spreads risks and faces competition. This study aims to identify the reality of bancassurance as a mechanism followed by insurance companies to distribute their insurance products through banks, in addition to the most important agreements that connect banks with insurance companies active in the Algerian market, highlighting the most important advantages that distinguish bancassurance as well as its reality in Algeria during the period extending from 2011 to 2022. The results were reached by the largest share achieved by the SAA Insurance Fund agreement under the control of two large branches, namely the automobile branch and the property damage insurance branch. Every year we see a clear dominance of these two branches, as they account for more than 83% of the premiums, and the percentage has increased to more than 80% since the year 2011. Until 2022."